High carriage rate of ESBL-producing enterobacteriaceae at presentation and follow-up among travellers with gastrointestinal complaints returning from India and Southeast Asia - Barreto Miranda, Isabel; Ignatius, Ralf; Pfüller, Roland; Friedrich-Jänicke, Barbara; Steiner, Florian; Paland, Matthias; Dieckmann, Sebastian; Schaufler, Katharina Anna Christina; Wieler, Lothar H.; Guenther, Sebastian; Mockenhaupt, Frank Peter (Journal of travel medicine, 2016)
Abstract. Background. International travel contributes to the spread of multidrug-resistant microorganisms including extended spectrum beta-lactamase-producing
Gesehen am 23.06.2020